Racial disparities in transjugular intrahepatic portosystemic shunt procedure outcomes - Donna Niedzwiecki; Andrew J Muir; James H Helzberg; Alice Parish; Charles Y Kim; Yuval A Patel; Julius M Wilder (BMJ Open Gastroenterology)
Objective The transjugular intrahepatic portosystemic shunt (TIPS) procedure is an important intervention for management of complications of portal hypertension. The objective of this study was to identify predictors of mortality from the TIPS procedure with a focus on race and ethnicity.Design TIPS procedures from 2012 to 2014 in the National Inpatient Sample were identified. Weighting was applied to generate nationally representative results. In-hospital mortality was the primary outcome of interest. χ2 and Student’s t-tests were performed for categorical and continuous variables, respectively. Predictors of mortality following TIPS were assessed by survey-weighted logistic regression.Results 17 175 (95% CI 16 254 to 18 096) TIPS cases were identified. Approximately 71% were non-Hispanic (NH) white, 6% were NH black, 16% were Hispanic and 7% were other. NH black patients undergoing TIPS had an in-hospital mortality rate of 20.1%, nearly double the in-hospital mortality of any other racial or ethnic group. NH black patients also had significantly longer median postprocedure and total lengths of stay (p=0.03 and p<0.001, respectively). The interaction of race by clinical indication was a significant predictor of in-hospital mortality (p<0.001). NH black patients had increased mortality compared with other racial/ethnic groups when presenting with bleeding oesophageal varices (OR 3.85, 95% CI 2.14 to 6.95).Conclusion This cohort study presents important findings in end-stage liver disease care, with clear racial disparities in in-hospital outcomes following the TIPS procedure. Specifically, black patients had significantly higher in-hospital mortality and longer lengths of stay. Further research is needed to understand how we can better care for black patients with liver disease.